Site-specific incorporation of 19F-nuclei at protein C-terminus to probe allosteric conformational transitions of metalloproteins - Xichun Liu; Pengfei Guo; Qiufan Yu; Shu-Qin Gao; Hong Yuan; Xiangshi Tan; Ying-Wu Lin (Communications Biology)
Abstract Allosteric conformational change is an important paradigm in the regulation of protein function, which is typically triggered by the binding of small cofactors, metal ions or protein partners. Here, we found those conformational transitions can be effectively monitored by 19F NMR, facilitated by a site-specific 19F incorporation strategy at the protein C-terminus using asparaginyl endopeptidase (AEP). Three case studies show that C-terminal 19F-nuclei can reveal protein dynamics not only adjacent but also distal to C-terminus, including those occurring in a hemoprotein neuroglobin (Ngb), calmodulin (CaM), and a cobalt metalloregulator (CoaR) responding to both cobalt and tetrapyrrole. In Ngb, the heme orientation disorder is affected by missense mutations that perturb backbone rigidity or surface charges close to the heme axial ligands. In CaM, the C-terminal 19F-nuclei is an ideal probe for detecting the binding states of Ca2+, peptides and inhibitors. Furthermore, multiple 19F-moieties were incorporated into the two domains of CoaR, revealing the intrinsically disordered C-terminal metal binding tail might be an allosteric conformational switch to maintain cobalt homeostasis and balance corrinoid biosynthesis. This study demonstrates that the AEP-based 19F-modification strategy can be applied to various targets to study allosteric regulation, especially for those biological processes modulated by the protein C-terminus.